Pengembangan Media Pembelajaran Menggunakan Metode Komputasi pada Sub Pokok Bahasan Haloalkana di SMA - Gayatri Marwan, Anastasia; Asep Wahyu Nugraha (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to determine the feasibility and student responses, from the development of learning media using computational methods. The subject of this research is molecular animation using computational methods. The object of this research is haloalkane material. This type of research is a development that refers to the ADDIE model. This study uses non-test instruments, non-test instruments used in the form of Validation Sheets that have met the BSNP standards by validators and Student Response Questionnaire Sheets. The results of the feasibility validation show that the development of animation learning media uses computational methods and is presented using Macromedia Flash. The average percentage of media expert validators' assessments on content feasibility is 88.25%, presentation feasibility is 87.5%, language eligibility is 88.25%, contextual aspects are 88.75%. And for the average percentage of media assessment on the aspect of influence on the strategy is 95%, the software engineering aspect is 92.5% and the visual and audio display aspect is 85%. As well as the results of the average percentage of student responses to learning media that is 92.6%.